Biochemical and clinical variations among severe Plasmodium Vivax malaria cases: A prospective study - Kundu, Dipankar; Sen, Santanu; Basu, Satyaki; Chhatui, Oindrila; Nag, Paromita; Ghosh, Joyraj (International Journal of Medical Research and Review, 2018)
Context: Plasmodium vivax is geographically widely distributed with up to 2.5 billion people at risk and an estimated 70-80 million cases every year. India contributes 77% of the total malaria in Southeast Asia. Retrospective analysis of burden of malaria showed that disability adjusted life years due to malaria were 1.86 million years. According to recent study, West Bengal contributes 11% of total malaria cases in country and is one of states where falciparum resistance to chloroquine has been confirmed. Aims: The aim of this study was to evaluate the biochemical and clinical profile of severe and non-severe Plasmodium vivax malaria and the complications and outcome of P. vivax malaria infections as there is very limited information on age and sex specific seasonal prevalence of malaria in different paradigms in the country. Materials and Methods: A hospital based prospective study was conducted in Medical College, Kolkata comprising of 138 patients with fever (≥37.5˚C), peripheral smear and/or rapid diagnostic tests positive for P. vivax. Previously established cases of CKD, hematological abnormalities, chronic liver diseases and neuro-psychiatric disorders were excluded from our study. Demographical, clinical and laboratory parameters including liver function test, renal function test were documented and were presented in tabular and statistical means. Results: Jaundice was present in 22% of patients and vomiting in 32% of the patients. Hepatomegaly was seen in 16 % cases and 33% cases had splenomegaly. ARDS was seen in 16% of severe malaria cases. Acute kidney injury was seen in 8% and cerebral malaria was seen in 12% of severe malaria cases. Multi organ dysfunction was seen in12 %cases. There was 1 death in the study due to multi organ dysfunction. Conclusion: Life threatening complications such as ARDS, AKI, cerebral malaria and MODS can be seen in P. vivax mono infections.